Lithuanian Phraseological Units in Gottfried Ostermeyer’s Works on Literary and Religious History - Aleknavičienė, Ona (Senoji Lietuvos literatūra, 2016)
The paper focuses on Lithuanian phraseological units found in Gottfried Ostermeyer’s (1716–1800) works on literary and religious history. In the broad sense, phraseology is understood as averbal instrument of nurturing, transmission, and content formation of cultural memory. In this paper the author shows how Ostermeyer, who chose Lithuanian studies (in the broad sense) for his scholarly work, appreciated phenomena of the living Lithuanian language and how he used phraseological units to justify his historical, literary, and linguistic arguments. The author pays much attention to the chronology of the records of the phraseological units: attempts are made to identify the units that Ostermeyer was the first to use. Since a considerable number of phraseological units have not been found in other sources (or, possibly, these sources have not survived), the ones used by Ostermeyer should be treated as the first currently known mention. Seven of them are inscribed in Jacob Brodowski’s collection of small genres of folklore Littauische Sprichwörter und Räthsel (Lithuanian Proverbs and Riddles; c. 1716–1744, Trempai; LMAVB RS: F 137–1): Dievas nežiūri į aruodą; Jau brauki su lapais, tikt šakučius palieki; Kas yra gražesnis po Smerčio, ne kai gyvas! [Response:] Vėžys; Skola ne moma; Svečias neilgai yra, ale daug mato; Tirpulys per mano kuną įėjo; Tinginį raginsi, be tojo (šiojo) pats dirbk; three in the treatise Kritischer Beytrag zur Altpreußischen Religionsgeschichte (A Critical History of the Old Prussian Religion; Marienwerder, 1775): Tai jau jo likimas; Laumės apmainytas; Kad tave Giltinė nusmaugtų; one in the treatise Gedanken von den alten Bewohnern des Landes Preußen (Thoughts on the Old Inhabitants of the Prussian Land; Königsberg and Leipzig, 1780): Trys kirtikai, trys rišikai, trys nešikai, o trys – juosta [Response:] Šienpjūvys. Other phraseological units are found in earlier books and manuscripts of Lithuania Minor. The purpose of the phraseological units in Ostermeyer’s works differs: (1) inscriptions in Brodowski’s Littauische Sprichwörter und Räthsel complement the number of phaseological units taken from spoken language and specify some of Brodowski’s notes; (2) in the polemical treatise Kritischer Beytrag zur Altpreußischen Religionsgeschichte (1775), they prove the existence and functions of the old Prussian gods; at the same time, justification is provided to the effect that the ancient religion is not imported; (3) in the treatise Gedanken von den alten Bewohnern des Landes Preußen (1780), the author demonstrates that Lithuanians have their own astronomical terms thus the names of celestial bodies are not borrowed from either the Gothic or Finnic languages; correspondingly, the Lithuanian language is not a mixture of various languages, contrary to the claims of professor Johann Thunmann of Halle University; (4) in the work Apologie des neuen Littauischen Gesangbuchs wider die Mielckischen Beschuldigungen (Apology of the New Lithuanian Hymnal against Mielcke’s Accusations; Königsberg, 1790–1791) the author seeks to justify the use of phraseological units of spoken language in written language, and (5) in the history of hymnals Erste Littauische Liedergeschichte (Königsberg, 1793) they explain the words seldom used in hymnals. The phraseological units found in the treatise Kritischer Beytrag zur Altpreußischen Religionsgeschichte point to the ancient mythological world- view. Continuous communication of the fragments of this world-view by verbal tradition (this is shown by the comments on usage accompanying the phraseological units) provided Ostermeyer with a footing to propose that such phraseological units were reliable facts that lie at the base of Lithuanian mythology and are capable of verifying the arguments put forward by earlier Prussian historians. Set phrases with the theonym Perkūnas are based on the written tradition. The fact of their inclusion in the work leads to the conclusion that Ostermeyer had a good knowledge of historical sources and a critical attitude to mythological claims. Set phrases featuring the names of pre-Christian gods, their sphere of activity, characteristic attributes, and hints to rites and other symbolic representation of the past provide information on the continuing association of the eighteenth-century society with the culture of the past and with sacral experience relevant to it. Set phrases associated with ancient Lithuanian deities Perkūnas, Laima, Laumė, or Giltinė support the fact that the myths of the past were still an important component of cultural identity in the second half of the eighteenth century. This makes it possible to approach the idiomatic phrases in Ostermeyer’s works – both the ones he had recorded from spoken language and taken from other sources – not only as facts of the Lithuanian language but also as instruments for the transmission of cultural memory. Having included them in his works, Ostermeyer had also placed them in the storage of cultural memory thus ensuring that the elements of the eighteenth-century world-view would be known in later times. Three phraseological units in Ostermeyer’s works contain the word Dievas (God), but only the maxim Dievas neveikus, ale atmenus (God is slow to act but remembers all) is attributable to the category of biblical idiomatic phrases. Meanwhile, the content of the good wish beginning with Dieve duok (God give/ let) – Dieve duok vienam gimt, ale ne vienam dirbt (God let be born alone but not work alone) and the proverb Dievas nežiūri į aruodą (God does not look into the granary) – is not religious but associated with practical activities and needs of the social layer that had created them, that is, the peasants. Phraseological units that found their way to literary works as a consequence of a polemic with Christian Gottlieb Mielcke and given in response to his critical remarks set out in Bescheidene Beantwortung des Bedenkens, so Herr Pfarrer Ostermeyer von Trempen über einen Entwurf zum neuen Littauischen Gesangbuch bekannt gemacht (A Modest Response to Pastor Ostermeyer’s Reflections on the Project for a New Lithuanian Hymnal; Königsberg, 1788), make it possible to reconstruct them in Ostermeyer’s lost hymnal. They highlight relevant stylistic issues of the hymns and stylistic differentiation of works in verse. Usage of phraseological units in the works on Lithuanian studies show Ostermeyer’s favourable attitude to the small folklore genres as ones that communicatesignificantand generalized experienceof the linguisticcommunity.